Investigation and analysis of Basketball as an extracurricular activity in middle schools in Beijing Tongzhou - Miao, X.L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: As an important extracurricular activity, basketball has played a key role in promoting physical exercise. However discrepancies are seen between rural and urban schools. This study investigates basketball in three town schools: Beijing Tongzhou Luhe Middle School, Yunhe Middle School, and Tongzhou No.2 Middle School; as well as three rural schools: Langfu Middle School, Chaichangtun Middle School and Zhaili Middle School. Methods A review of literature was conducted, questionnaires were distributed, experts were consulted, and students and teachers were visited in the six above-mentioned middle schools. Results It was found that basketball as an extracurricular-activity was more popular in Tongzhou schools than rural schools with regard to facilities, participants, qualified teachers and organization. The results of the questionnaire revealed a number of reasons for this current situation: the concern of leaders and students, student`s motivation to participate in the organization of extracurricular-activities in each school, student`s exercise goals, the condition of the school`s equipment and the organization of basketball matches.